Adsorption of Cd(II) and Pb(II) onto a one step-synthesized polyampholyte: Kinetics and equilibrium studies - Copello, Guillermo Javier (2012)
A one step-synthesized polyampholyte, bearing carboxylate and 2-methylimidazole (2MI) groups, was tested as adsorbent for the removal of Pb(II) and Cd(II) from aqueous solutions. This material combines the benefits of synthetic polymers, such as high adsorption capacity and chemical stability, and the advantages of biosorbents in regard of costs and simplicity of the production.The short time needed to achieve the adsorption equilibrium indicated a chemical-reaction controlled process. A network expansion was predicted as a result of repulsive interaction between the fixed positive charges.Langmuir model presented the best fitting to isotherm equilibrium data, with a maximum adsorption capacity of 182mgg -1 for Cd(II) and 202mgg -1 for Pb(II). The metal removal was strongly dependent on pH, involving carboxylate and 2MI residues. An ion-exchange process for Pb(II) and Cd(II), combined with coordination for the later, were the most probable mechanism of interaction. The adsorption of 1.35ppm Cd(II) was 72±6% in well-water, and the adsorption of 0.50ppm Pb(II) was 62±5% in tap-water. The recovery figures for Cd(II) in 1% HNO 3 were optimal.